Sustainable environment in the classroom: Exploring environmental socioscientific issues (ESSI) using Mongabay online news site - Marlina Ummas Genisa; Erni Angraini (JPBI (Jurnal Pendidikan Biologi Indonesia), 2023)
Environmental issues in online newspapers allow environmental course instructors to examine social scientific topics in a sustainable. However, it remains a problem for instructors to fully examine the dimensions of knowledge connected to the environment in online newspapers. The purpose of this research is to develop a fundamental framework for studying scientific information in online newspapers that can be integrated into the curriculum and utilized successfully to foster environmentally conscious young people. The exploratory process utilizes Robert N. Entman's framing analysis model combined with Bloom's taxonomy. According to Bloom's taxonomy, framing has two dimensions: environmental issue selection and issue emphasis, which is centered on the knowledge dimension. The findings indicate that the Mongabay media, in generating news about environmental concerns such as mangrove degradation can highlight the full aspects of environmental knowledge, allowing it to be utilized as a medium for environmental learning in the classroom. However, the information presented on Mongabay media reveals more of the dimension of knowledge at a factual level only. Therefore, it is still to enrich material especially that which is not presented in the news to explore conceptual and procedural dimensions.